Clinical Significance of Intravesical Prostatic Protrusion in Patients with Benign Prostatic Hyperplasia - Sigdel, Ghanshyam; Belokar, WK (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Intravesical prostatic protrusion is a morphological change due to excessive growth of the median and lateral lobes of the prostate into the bladder in benign prostatic hyperplasia. It causes a 'ball-valve' type of obstruction during voiding. It is a useful parameter to assess the severity of the disease process, selection of treatment modality and its possible outcome in benign prostatic hyperplasia. MATERIAL AND METHODS: A prospective, non-randomized, observational study was carried out from January 2014 to June 2014 in the Department of Urology, College of Medical Sciences, Nepal. Total of 50 patients with benign prostatic hyperplasia were evaluated to assess the correlation of intravesical prostatic protrusion with international prostate symptom score, prostate volume, maximum flow rate and post void residual urine. Correlation between parameters of interest was quantified with Pearson correlation test. RESULTS: A positive correlation was demonstrated between intravesical prostatic protrusion, international prostate symptom score, prostate volume and post void residual urine. There was a negative correlation between intravesical prostatic protrusion and maximum flow rate. CONCLUSION: Intravesical prostatic protrusion is correlated with international prostate symptom score, prostate volume, maximum flow rate, and post void residual urine volume and hence can be used to assess the severity of benign prostatic hyperplasia. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 6-10